2014
DOI: 10.2147/cia.s68193
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and tolerability of saxagliptin add-on therapy in older patients (aged ≥65 years) with type 2 diabetes

Abstract: BackgroundTreatment decisions for older patients with type 2 diabetes mellitus must balance glycemic control and adverse event risk. The objective of this study was to evaluate the long-term safety and tolerability of saxagliptin 5 mg as add-on therapy to common antihyperglycemic drugs in patients aged ≥65 years and <65 years.MethodsPooled adverse event data from three placebo-controlled trials of 76–206 weeks’ duration in older (≥65 years) and younger (<65 years) patients receiving saxagliptin 5 mg or matchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…Results from global Phase III clinical studies have demonstrated that a dosage of 5 mg once daily can significantly decrease HbA1c and FPG and PPG concentrations in patients with T2DM . Moreover, saxagliptin has proved to be well tolerated in patients with T2DM, including those with renal impairment and elderly patients (≥65 years of age) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from global Phase III clinical studies have demonstrated that a dosage of 5 mg once daily can significantly decrease HbA1c and FPG and PPG concentrations in patients with T2DM . Moreover, saxagliptin has proved to be well tolerated in patients with T2DM, including those with renal impairment and elderly patients (≥65 years of age) …”
Section: Discussionmentioning
confidence: 99%
“…5,[8][9][10][11] Moreover, saxagliptin has proved to be well tolerated in patients with T2DM, including those with renal impairment 12,13 and elderly patients (≥65 years of age). 14,15 Saxagliptin was approved in China in May 2011 for the treatment of T2DM, either as monotherapy or added to metformin. Although several studies of saxagliptin have been undertaken in China, [16][17][18] there is still a lack of data supporting its efficacy and safety from large-scale clinical trials in Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neither age nor sex was identified as a significant covariate in the apparent clearance of saxagliptin or 5-hydroxy saxagliptin in population pharmacokinetic analyses [7,33]. The \2-fold difference in saxagliptin systemic exposure between older and young individuals and the favourable safety and tolerability profile observed in people C65 years old when saxagliptin was used as monotherapy or add-on therapy [34][35][36][37] suggest that age alone does not warrant dose adjustment. The small difference in 5-hydroxy saxagliptin exposure in female subjects compared with male subjects does not warrant dose adjustment.…”
Section: Influence Of Demographic Variablesmentioning
confidence: 99%
“…Disponemos ya de estudios en personas mayores de todos ellos que apoyan su eficacia hipoglicemiante y seguridad [67][68][69][70][71][72][73] . Tres de estos estudios se realizaron en pacientes con 70 o más años de edad 67,68,73 .…”
Section: Fármacos Incretínicosunclassified